Radiocesium sorption-desorption processes in lake sediments - Ioannides, K.G.; Mertzimekis, T. J.; Karamanis, D.T.; Stamoulis, K.C.; Kirikopoulos, I. (J. Radioanal. Nucl. Chem., 1996)
The kinetics of radiocesium sorption and desorption by cation solutions and the corresponding radiocesium distribution profiles in sediment cores were investigated. The results have shown that a significant percentage of radiocesium is adsorbed in the sediments during the first 3 d. Radiocesium reaches rapidly (< than 5 d) at a depth which does not exceed 3.5 cm. The desorption of radiocesium was found to depend on cation concentrations. Empirical laws are derived both for cesium adsorption and desorption.
Keywords: Adsorption; cesium 137; conference paper; desorption; ion exchange; Pollution; sediment